Embedded Device Berbasis PLC pada Miniatur Konveyor untuk Pengoperasian Simulator Rejection System - Muhamad Wildan; Arief Goeritno; Joki Irawan (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
A PLC-based embedded device on a miniature conveyor machine for operating a rejection system has been designed and constructed. The research objectives, namely (i) design and manufacture of an integrated system, (ii) making program structure based on a ladder diagram, and (iii) measuring the performance of an integrated system. Integrated system assembled from a miniature of the conveyor machines and belt installation, and installing the dc motor, while the rejection system assembly by placing several sensors, installing stepper motor, and wiring to the PLC system. Programming based on ladder diagram carried out by determining algorithms, compiling the ladder diagram, addressing the input/output, and compiling and uploading the program from PC to PLC. The performance of the integrated system was observed when (a) observation during synchronization, (b) observations of sensor readings while the rejection system simulator is operating, and (c) observation and measurement of the processing time of the rejection arm. Overall results have been obtained in the form of a PLC-based embedded device for the rejection system simulator on observations of the condition of the bottle caps for beverage packaging. Based on the overall observation, the PLC-based embedded device has functioned to operate the rejection system can be implemented at a manufacturing scale.